Enhancing learning in higher education: factors and methodology - Duzhyk, Nataliia (My University, 2021)
The purpose of this paper is to identify factors and methods enhancing the quality of learning in a university setting. It is pointed out that an overcritical attitude towards learners’ incompetent public performance may cause anxiety and hinder their learning. However, group participation facilitates developing students’ self-expression and life skills. Traditional views on teaching are evaluated with regard to the latest pedagogical trends.The methodology of the paper relies on observation of the educational process, theoretical analysis of common and emerging frameworks for teaching English as a second language in a university setting, as well as synthesis, and generalization of research literature findings.The paper demonstrates how a traditional framework for teaching English as a second language can be modified to accommodate learners’ needs and investigates how innovative methods and technologies affect teaching of a foreign language and development of students’ foreign language competence. It is shown that lessons incorporating pre-communicative and communicative activities can be structured differently. The key to successful learning by a group of students is to take into consideration the quality of tasks and to present materials in a flexible manner to the learners.Our examples are based on fundamental principles, such as a variety of tasks, repetition and internationalization of the content. For warm-up or pre-communicative activities, we choose tasks preparing students for speaking and building their language competence. A number of “silent” activities enable learners to perform more or less simultaneously in order to lay the foundation for their internal language representation in an atmosphere free from anxiety and distraction. After completing exercises, students are expected to utilize previously learned grammar and vocabulary in their speech.
Keywords: technology-enhanced learning; вивчення іноземної мови; цифрові технології навчання; кафедра ділової іноземної мови та міжнародної комунікації